MENINGKATKAN MOTIVASI BELAJAR ANAK MELALUI METODE PERMAINAN DARI BAHAN BEKAS PADA KELOMPOK B DI KELOMPOK BERMAIN DHARMA MULYA TENGGARONG SEBERANG TAHUN PELAJARAN 2016/2017 - Hakimah - Hakimah; Harry - Gunawan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
This study concerns with students’ low learning motivation issue. At the preliminary observation, only 33.3% students were reported to be in the good level of learning motivation. Moreover, classroom action research was conducted to reveal the effectiveness of using used materials as teaching aids in terms of promoting students’ learning motivation. In this study, the researcher applied two cycles, wherein, each cycle consists of planning, implementation, observation and reflection. Observation and documentation were employed to collect data. Meanwhile, percentage technique was used to analyze the data. In addition, this study involved 30 students of Dharma Mulya Playgroup. The first cycle shows progress with 47% students reached the passing grade that falls into fair criteria. However, at the second cycle, students’ progress in motivation increased, since 85.6% students had achieved the passing grade and were categorized in very good criteria. In conclusion, using used materials in teaching (as a method of playing) was able to promote learning motivation of Group B at Dharma Mulya Playgroup Tenggarong Seberang.